Survival and dispersal of Isariopsis indica var. zizyphi causing mouldy leaf spot of Ber - SANJIV KUMAR, K.S. VERMA and (Indian Phytopathology, 2002)
Studies on the survival of Isariopsis indica var. zizyphi by subjecting the infected leaves with typical leaf spots to different storage conditions up to 180 days revealed that the pathogen survives under natural conditions on the infected leaves either falling on the ground or sticking to crotches of branches and cracks on the bark. Trapping of maximum number of conidia on aeroslides facing south-west and west-north directions confirmed the role played by wind currents in the initiation of primary infection and secondary spread of the disease.